Drawing down the moon : witches, Druids, goddess-worshippers, and other pagans in America - Adler, Margot (Penguin Books, 2006)
Almost thirty years since its original publication, Drawing Down the Moon continues to be the only detailed history of the burgeoning but still widely misunderstood Neo-Pagan subculture. Margot Adler attended ritual gatherings and interviewed a diverse, colorful gallery of people across the United States, people who find inspiration in ancient deities, nature, myth, even science fiction. Contrary to stereotype, what Adler discovered was neither cults nor odd sects, but religious groups that are nonauthoritarian in spirit and share the belief that there is no one single path to divinity.